Det "upphävbara" gynnande förvaltningsbeslutet - En analys av lagförslaget om att återkalla det svenska medborgarskapet i relation till gynnande förvaltningsbesluts orubblighet - Almqvist,Alice (2025)
This thesis is an analysis of a legislative proposal presented in an official inquiry from 2025 about fundamental freedoms and rights. The proposal suggests that an opportunity to revoke the Swedish citizenship should exist in the Swedish constitution, something that is not possible with today’s legislation. The acquisition of citizenship through naturalization is an administrative de- cision that gives the individual several rights. The focus of this thesis is to examine the relation between such an administrative decision and the nega- tive legal effect that these decisions have which arise when talking about re- voking citizenship. In order to understand how the legislative proposal will be used the thesis studies two of the legal criteria concerning how the citizenship can be revoked if acquired through false information or improper conduct. The thesis concludes that the legal criteria presented in the legislative proposal are vague and unclear. This entails a risk of an arbitrary application of the law which would decrease the level of legal certainty. Moreover, a consequence of introducing the legislative proposal could be that two types of Swedish citizenship is created, one that can be revoked through the constitution for those with more than one citizenship and one that cannot. This could be the result of the fact that the authorities can change a favourable decision which is constitutionally protected to the disadvantage of the individual, something that this legislative proposal enables. In summary the proposal implies an increased flexibility to change decisions made on inaccurate grounds, but at the same time it can result in an unclear application of the law.
Keywords: förvaltningsrätt; medborgarskap; gynnande förvaltningsbeslut